Bacterial etiology of acute diarrhea in Vietnamese children under five: A cross-sectional study using real-time polymerase chain reaction - Tran, Khai Quang; Nguyen, Uyen Thi Phuong; Le, Loan Thi Thuy; Nguyen, Nhi Thi Yen; Nguyen, Hung Hoang Tuan (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Bacterial acute diarrhea remain a significant health concern in Vietnam, necessitating further research on infection prevalence and clinical characteristics in pediatric patients. This study aimed to determine the prevalence of bacterial pathogens using real-time polymerase chain reaction and to describe clinical and paraclinical characteristics associated with bacterial infections. Methods: This cross-sectional study was conducted on 271 children diagnosed with acute diarrhea at Can Tho Children’s Hospital between November 2022 and July 2023. Results: Bacterial pathogens were identified in 45.4% of cases, with Escherichia coli (18.5%) being the most prevalent, followed by Salmonella spp. (10.7%) and Clostridium difficile (8.5%). E. coli infection was significantly associated with fever (p=0.012), while Salmonella sp. was linked to vomiting (p=0.004) and loose watery stools (p=0.008); Vibrio cholerae infection showed a significant correlation with dehydration (p=0.028). Additionally, C. difficile infections were associated with a higher white blood cell count compared to the uninfected group (p=0.017). Multivariable analysis showed that elevated WBC and fever with E. coli (aOR=3.39 and 0.15), vomiting and watery stool were associated with Salmonella spp. (aOR=2.54 and 2.71), and dehydration with V. cholerae (aOR=8.92). Conclusions: Clinical features such as fever, vomiting, and leukocytosis showed associations with presumed bacterial etiology in pediatric diarrhea. However, these exploratory findings are hypothesis-generating and do not support diagnostic or therapeutic decisions. Microbiological confirmation remains essential for accurate etiologic diagnosis and appropriate clinical management.